Global trade and water: lessons from China and the WTO - Liao, Yongsong; Fraiture, Charlotte de; Giordano, Mark (2008)
Agricultural trade and water use are intrinsically linked. The case of China illustrates how (1) trade liberalization may impact water use; and (2) failure to consider water resources may distort analysis of trade liberalization. This article incorporates water constraints into forecasts of future agriculture in China and thereby creates a new set of scenarios that explicitly examine linkages between agriculture, water, and global trade. These new assessments show that many existing projections regarding agriculture in China are unrealistic due to water scarcity. For instance, China may import more wheat and export fewer vegetables and fruits than has typically been predicted. The findings also indicate that WTO accession provides China with opportunities to better manage demand for water in its agricultural sector while still addressing key food security concerns. The article emphasizes that it is crucial to include water as a factor of production when analyzing global agricultural trade. Global governance mechanisms of trade, such as the WTO, need to fulfill their key role in the design of effective water resources policy.